vascular hemiplegia - Voto Bernales, Jorge (1955)
The vascular hemiplegia is the functional disorder of a lateral half of the body produced by alterations of cerebral vessels. Should review the concepts of this common condition, with the dual aim of expanding its nosographic value and considering the hemiplegic patient as worthy of the highest professional care